NSIDC Meteorological Data from the Russian Arctic, 1961-2000 - NASA National Snow And Ice Data Center Distributed Active Archive Center; RU/FSR/HME/AARI (UCAR/NCAR - Research Data Archive, 2007)
"This data set contains monthly means of meteorological observation data from Russian stations from 1961-2000 (for most stations). The Russian station observations were provided by Vladimir Radionov, Arctic and Antarctic Research Institute (AARI), St. Petersburg, and include 2-meter air temperature, sea level pressure, total and low cloud amount, precipitation, and relative humidity. Data are available in ASCII text format via FTP.", quoted from NSIDC site.The data files and associated documentation were downloaded to this DSS site in January 2007. See the dataset documentation [http://rda.ucar.edu/datasets/ds489.0/#!docs] for more information.